Implementasi Manajemen Pendidikan Islam dalam Meningkatkan Peran Guru Pendidikan Agama Islam di PKPPS Minhajurrosyidin Jakarta Timur (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the urgency of effective Islamic Education Management (MPI) as a prerequisite for enhancing the role of Islamic Education (PAI) teachers in shaping students’ religious character amid the challenges of digitalization and institutional coordination constraints. The purpose of this study is to analyze the implementation of MPI experienced by PAI teachers, the interaction among stakeholders, and the teachers’ perceptions of its effectiveness at PKPPS Minhajurrosyidin, East Jakarta. Using a descriptive qualitative method with a case study and phenomenological approach, data were collected through triangulation (interviews, observations, and document studies) and analyzed using the Miles and Huberman interactive model. The findings indicate that MPI is an essential structural mediating variable. The optimization of MPI—particularly in terms of digital facility support and professional training—significantly enhances the effectiveness of PAI teachers as Uswah Hasanah and as facilitators of adaptive and scientific learning. However, the main obstacle lies in the lack of horizontal coordination among teachers in holistically integrating Values-Based Education. The implications of this study emphasize the need for formal managerial policies to ensure collective responsibility in character formation.